Transcriptional Expressions of ALDH1A1/B1 as Independent Indicators for the Survival of Thyroid Cancer Patients - Cui, Ying; Liu, Yao; Mu, Lan; Li, Yang; Wu, Gang (Frontiers in Oncology, 2022)
Background: Aldehyde dehydrogenase (ALDH) 1 is an important enzyme involved in the regulation of several cellular mechanisms via aldehyde detoxification. High ALDH1 levels were correlated with tumorigenesis and stemness maintenance in cancer. Methods: We used UALCAN, Human Protein Atlas, Kaplan-Meier Plotter, TISIDB, TIMER, and KOBAS databases to investigate the expression and role of ALDH1 in thyroid cancer progression. In addition, quantitative real-time polymerase chain reaction was performed to detect the expression of the target genes in thyroid cancer cell lines and cancer tissues. Results: Expression of ALDH1A1/B1 was significantly decreased based on individual cancer stages and tumor histology, and high levels of ALDH1A1/B1 were associated with poor overall survival in thyroid cancer patients. Moreover, ALDH1A1/B1 expression was negatively correlated with immune stimulating genes, major histocompatibility complex, chemokines, and receptors. Conclusions: These results suggest that ALDH1A1/B1 might serve as potential prognostic biomarkers and novel immunotherapeutic targets for thyroid cancer treatment.